Acute effect of ischemic preconditioning is detrimental to anaerobic performance in cyclists - Paixão, R. C.; da Mota, G. R.; Marocolo, M. (International Journal of Sports Medicine, 2014)
We verified the acute effect of ischemic preconditioning (IPC) in cyclists before high-intensity and short-duration activity. 15 amateur cyclists participated in a random crossover model on 2 different days [IPC or CONTROL (CON)]. Ischemic preconditioning consisted of 4 cycles of 5 min occlusion/5 min reperfusion in each thigh. After IPC or CON, volunteers performed a series of Wingate tests to evaluate anaerobic performance (maximal [Pmax] and medium [Pmed] power output, total anaerobic power, and fatigue index). Blood lactate concentrations were assessed at 6 min after each Wingate test. Ischemic preconditioning decreased Pmax (p<0.05), Pmed (p<0.01), and total anaerobic power (p<0.01) in the first Wingate, and decreased Pmed (p<0.01) and total anaerobic power (p<0.01) in the second Wingate (p<0.01). No significant differences were found in blood lactate or fatigue index between IPC and CON. In conclusion, our results indicate that IPC has a detrimental acute effect on anaerobic performance in amateur cyclists. Compared with positive results of previous studies, the effect of IPC seems to be dependent on the type of exercise.